Hukum "Money Laundering" Indonesia - Mamang, Damrah (LAW REVIEW, 2003)
The concrete activity against money laundering has become internationally concenrn  since the establishment of UN Drug Convention in 1988, in Vienna, Switzerland. The  UN Drug Convention signed by 106 states and it is basically used as ground for the  supervition over money laundering activities in many countries. The Anti Money  Laundering has also become the concern of bank or financial institution since the existence of Basle Committee on Banking Regulation and Supervision Practice which recommend that the bank should pay attention and make necessary regulation to record customer identification properly. In the money laundering combat, G-7( Group Seven ) founded the International body Anti Money laundering known as the Financial Action Task Force on Money laundering ( FATF) and drawn up the Forty Recommendation in  1990 and then it revised in 1996. As a part international community, Indonesia should  actively participate in every effort againts money laundering nationally and multilateral.  In general, Money Laundering as certain process or activity executed by a person or  criminal organization towards money originating from a criminal offense, which has the  intention to hide the source of this money from the government or organization authorized  to take actions againts this criminal offense, which makes mainly use of the method to  distribute the money into the financial system, thereafter resulting this dirty money, when  retrieved from the financial system, to be clean and legal. Meanwhile, Bank Indonesia (  the Central Bank )asa control institution of the banking system in Indonesia, has released  a regulation No. 3/10/PBI/2001 consisting of Know Your Customer ( KYC) as a part  of government concern to prevent national banking system monyel laundering. The  regulation has been suported by international recommendation as avowed by the Basle  Committee on Banking Supervision and the FATF.